Konformitas Teman Sebaya dengan Kecenderungan Kecanduan Media Sosial Tiktok Pada Komunitas Remaha di Seberang Ulu 2 Palembang - Anjani Puspitasar; Mulia Marita Lasutri Tama (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2021)
This study aims to determine the relationship between peer conformity and the tendency to become addicted to social media tiktok in the youth community across Ulu 2 Palembang. This research was conducted on teenagers in the tiktokcrew community to see the high and low peer conformity that affects the tendency to become addicted to tiktok social media. This study uses quantitative research methods, while the data collection used purposive sampling technique. The subjects of this study were 152 subjects who became members of the tiktokcrew community. measurements were carried out using a Likert scale measuring instrument Analysis of the results of this study using SPSS version 20.0 analysis. there are regression results showing r = 0.824 r2 = 0.678 P = 000 (p <0.05). The results of the analysis obtained indicate that there is a very significant relationship between peer conformity and the tendency of tiktok social media addiction of 67.8%, thus the proposed hypothesis is accepted.